LAND ASSET DISPUTE SETTLEMENT SCHEME LINKED TO THE PRINCIPLE OF JUSTICE - Riza Zulfikar (SEAN Institute, 2023)
One of the existing land problems is land problems arising from the control and management of land by the Regional Government, both land that has become an asset and land that is recognized as Regional Asset Land. The purpose of this study is to understand the provisions of the law governing the authority of local governments in resolving regionalt land asset disputes. This dissertation research is normative legal research through statutory, conceptual, case and comparative approaches as well as the application of legal theory in assessing legal opportunity, justice and legal certainty, in the mechanism and process of settling disputes over land rights over assets. The results of the study show that the settlement of land asset disputes is one of the concurrent government affairs between the Central Government and Regional, Provincial, Regency/City Governments based on the principles of accountability, efficiency and externality, as well as national strategic interests. In settling disputes over land assets, the Regional Government is obliged to use and utilize and manage the land by securing and controlling the assets, both administratively and juridically according to the principles of justice and legal certainty. A comprehensive and effective mechanism is needed to prevent and resolve disputes over state/regional property land through an integrated, integrated and coordinated resolution of state/regional property land disputes between Ministries/Agencies, Regional Governments, Law Enforcement Officials, which is manifested in the form of a joint agreement that set forth in Regional Regulations, Governor/Mayor/Regent Decisions regarding Integrated and Coordinated Land Dispute Settlement Teams, so that joint agreements can encourage the recognition of these institutions for the results of asset land dispute resolution based on authority in the Dispute Settlement Scheme.